Worldwide Greenhouse Gas Reduction Potentials in Transportation by 2050. (28th December 2015) - Taptich, Michael N.; Horvath, Arpad; Chester, Mikhail V.
Summary: Reductions in the greenhouse gas (GHG) intensity of passenger and freight transportation are possible through adoption of fuel‐saving technologies, demand switching between modes, and large‐scale electrification of fleets, in addition to other actions. In this study, future scenarios to 2030 and 2050 are the basis for assessment of GHG reduction potentials for major passenger and freight modes (automobiles, buses, trains, aircraft, and oceangoing vessels) across eight regions of the world. New fuel‐saving technologies can significantly reduce the life‐cycle GHG footprint of both passenger and freight vehicles, but not uniformly worldwide. Countries outside of the Organization for Economic Cooperation and Development (OECD) lag behind OECD countries in GHG reduction potentials for all modes but oceangoing vessels owing to a combination of slower adoption of fuel‐saving technologies and a slower decarbonization of electricity generation and other processes. The reduction of GHG intensity will occur more slowly for freight modes than for passenger modes. However, improved fuel efficiency has negative feedbacks to the effectiveness of mode‐switching and alternative fuel adoption policies through 2050 because improvements in the fuel efficiency of vehicles alone may cause the marginal benefits of GHG abatement policies to diminish over time. This trend may be reversed if alternative fuel pathways decarbonize at faster rates than conventional transportation fuels. The largest opportunities for GHG reductions occur in non‐OECD countries. Given the many factors that distinguish transportation systems between developed and developing nations (e.g., availability of new technologies, the financial ability to acquire them, and policies to incentivize their adoption), many benefits could be gained through interregional cooperation.